2007
DOI: 10.1128/aem.01950-06
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Shiga Toxin-Producing Escherichia coli stx 1 , stx 2 , eaeA , and rfbE Genes and Survival of E. coli O157:H7 in Manure from Organic and Low-Input Conventional Dairy Farms

Abstract: Manure samples were collected from 16 organic (ORG) and 9 low-input conventional (LIC) Dutch dairy farms during August and September 2004 to determine the prevalence of the STEC virulence genes stx 1 (encoding Shiga toxin 1), stx 2 (encoding Shiga toxin 2), and eaeA (encoding intimin), as well as the rfbE gene, which is specific for Escherichia coli O157. The rfbE gene was present at 52% of the farms. The prevalence of rfbE was higher at ORG farms (61%) than at LIC farms (36%), but this was not significant. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 59 publications
2
53
2
Order By: Relevance
“…They represented that 54.54% of E. coli isolates were STEC. In addition to our results and also finding of Momtaz et al, 13 Hemmatinezhad et al 14 and Ranjbar et al, 15 simultaneous presences of stx1, stx2, eaeA and ehly virulence factors have also been reported by Franz et al, 17 JayRussell et al 18 and Kabiru et al 19 …”
Section: Discussionsupporting
confidence: 63%
“…They represented that 54.54% of E. coli isolates were STEC. In addition to our results and also finding of Momtaz et al, 13 Hemmatinezhad et al 14 and Ranjbar et al, 15 simultaneous presences of stx1, stx2, eaeA and ehly virulence factors have also been reported by Franz et al, 17 JayRussell et al 18 and Kabiru et al 19 …”
Section: Discussionsupporting
confidence: 63%
“…According to the National Organic Program regulations, ''proper'' composting implies that the stored manure reach a temperature above 55uC for several continuous days, depending on the level of aeration (stacked manure must be turned). The length of time needed to reach a satisfactory reduction of pathogens after fertilization depends also on the initial concentration in the manure (12), which again partly depends on the source, age, and storage conditions of the manure (19,26,39). Storage of manure with no continuous input will decrease pathogen numbers, but the rate of decline varies due to the composition of the manure, temperature, and other physicochemical factors (5).…”
Section: Resultsmentioning
confidence: 99%
“…Animal manure is a potential source of zoonotic pathogens such as Salmonella, Campylobacter, verotoxinproducing E. coli, and protozoan parasites, because many animals shed these pathogens asymptomatically in their feces (2,19,27). Pathogens persist in manure for a variable length of time, depending on the storage conditions, e.g., in stacked heaps or slurry tanks, which affect heat development, a main determinant of pathogen survival (5,20,22,26,39).…”
mentioning
confidence: 99%
“…In this context, the microbial communities that established after soil fumigation were shown to determine the fate of the invading species, whereby reduction in microbial diversity due to progressively enhanced fumigation depths resulted in higher pathogen persistence in soil (21). Similarly, in 25 different manures, the decline rate of E. coli O157:H7 was negatively correlated with Enterobacteriaceae richness (22). Furthermore, the easily available carbon content of the manure explained this decline rate (22).…”
mentioning
confidence: 87%
“…Similarly, in 25 different manures, the decline rate of E. coli O157:H7 was negatively correlated with Enterobacteriaceae richness (22). Furthermore, the easily available carbon content of the manure explained this decline rate (22). A study in organic manure-amended soil showed a faster pathogen decline when rates of nutrient flow were reduced (23).…”
mentioning
confidence: 94%